The Exploring the Impact of backwash through task-based instructional method in English Language Learning - Mooneeb Ali, Muhammad; Khizar, Nyla Uzma; yasmeen, Tayyaba (Journal of Peace, Development and Communication, 2020)
This research attempts to search out the effect of backwash in the process of task- based methods of learning on the vocabulary development of learners. The populace of this study comes from Pakistan are studying in an ELC (English Language Center). The sample size for the current study is 40 learners, without gender discrimination. The Learners were divided equally into binary groups i.e. controlled as well as the experimental. The earlier group was taught by conventional methods whereas the experimental was instructed through the task-based method of insruction. The time for each class was Sixty Minutes and overall process of learning was of twelve classes.The frequency of sessions was three times in a week. For analyzing the groups a pre test comprising of vocabulary items was taken from both groups and after the twelve sessions, a post test was also piloted on indistinguishable pattern. SPSS was applied and Independent sample (T-test) was utilized for analyzing the obtained data. The results revealed marked change in the performance of the two groups. It was explored that participatns of experimental groups outperformed the conventional learners of controlled group. These findings vividly suggest that task- based instructional method of learning has a significant influence of EFL students’ learning in terms of development of vocabulary. Keywords: Task based learning instruction, backwash, EFL students, vocabulary learning,